Environmental law for the construction industry - Stubbs, Amanda (Masons' guide., 2002)
This is an introduction to the wide subject of environmental law as it affects the construction industry. Changes in the structure of contracting arrangements have meant that those traditionally concerned with the construction process must now take greater interest in environmental law. In addition there is now a mass of regulation, governing matters such as waste management, water pollution, noise and other nuisances that have to be adhered to in practice.